Yudhishthira's Wisdom and Emerson's Brahma: The Power of Self-restraint/Samyama and the Awakened Soul - Dahal, Alisha (Shahid Kirti Multidisciplinary Journal, 2024)
This research examines how wisdom and "brahma" are instrumental in handling critical situations and adverse moments in life as portrayed by Yudhisthira in "Yudhisthira's Wisdom" and Brahman in Emerson's poem "Brahma". The Pandavas regains their lost lives because of Yudhisthira's restrained emotions and calm response to Yaksa's ordeal of answering his questions. Ralph Waldo Emerson's character Brahma also stands for an awakened self that sees beyond sensory things, finds oneness in dualities so can accept death as a part of life itself. Such a supreme self keeps a person in a state of mind which transcends all kinds of differences and brings in the realization of meaninglessness of the transient realities and sensory perceptions. To substantiate the argument that wisdom and brahman are the spiritual forces within us, this paper uses Heinrich Zimmer, Vivekananda and Radhakrishnan's interpretations of the holy book of Gita and its life lesson about Samaya. Few critics' insights regarding Emerson's "brahma" are also borrowed to support the proposition that the ultimate Truth termed variously as Soul, Supreme Self, Awakened Soul, Brahman and others is within us--omnipresent and imperishable. In a world where cruelty, violence, political and religious outrages, and technological disasters are mocking humanity; love, harmony and peace, this research can help to inculcate in people peaceful ways of resolving crises, the art of surviving them and coping with great dilemmas of lives.